Association between body mass index and diabetes mellitus in tuberculosis patients in China: a community based cross-sectional study - Jing Cai; Aiguo Ma; Qiuzhen Wang; Xiuxia Han; Shanliang Zhao; Yu Wang; Evert G. Schouten; Frans J. Kok (BMC, 2017)
Abstract Background We planned to determine the association of body mass index (BMI) with diabetes mellitus (DM) and impaired fasting glucose (IFG) in Chinese pulmonary tuberculosis (PTB) patients. Methods 3,505 newly-diagnosed PTB patients registered in PTB clinics in Linyi of China between September 2010 and March 2013 were enrolled. DM and IFG were identified based on fasting plasma glucose levels. ROC analysis was used to predict the ability of screening of BMI for DM and IFG in PTB patients. Results Compared with 18.5-23.9 kg/m2, patients with DM and IFG had significantly increased trends when BMI ≥ 24.0 kg/m2, and aORs were 2.28 (95%CI 1.44-3.60) and 1.30 (95%CI 1.04-1.64), respectively. After adjustment for age, gender, and educational level, there was an increased odd in BMI ≥ 23.41 kg/m2 for IFG, and a decreased odd in BMI < 19.82 kg/m2 for DM (p < 0.05). The cut-offs of BMI for screening IFG and DM in PTB patients were 22.22 kg/m2 (AUC 0.56) and 22.34 kg/m2 (AUC 0.59). Conclusions In PTB patients, BMI is significantly associated with IFG and DM. However, the predictive power of BMI was not sufficient, so it may only be a limited screening tool for DM and IFG among PTB patients in China.